Quality of social housing in Metropolitan Lima - Sanchez Barrera, Julio Cesar (2020)
ABSTRACT This article studies the quality and the satisfaction variables of the current situation as the housing in Metropolitan Lima, the Peruvian city with the highest population number, the largest number of homes from self-construction and, the lack of land to build new houses. Two instruments were designed to measure each one of the variables, and research was required to have a quantitative, transversal, and non-experimental approach. This study verified the direct relationship that exists between the variables and had determined the current state of each one. Besides, they will rank the dimensions of satisfaction for housing quality.